A High-Throughput Method for Illumina RNA-Seq Library Preparation - Kumar, Ravi; Ichihashi, Yasunori; Kimura, Seisuke; Chitwood, Daniel H.; Headland, Lauren R.; Peng, Jie; Maloof, Julin N.; Sinha, Neelima R. (Frontiers in Plant Science, 2012)
With the introduction of cost effective, rapid and superior quality next generation sequencing (NGS) techniques, gene expression analysis has become viable for labs conducting small projects as well as large-scale gene expression analysis experiments. However, the available protocols for construction of RNA-Sequencing (RNA-Seq) libraries are expensive and/or difficult to scale for high-throughput applications. Also, most protocols require isolated total RNA as a starting point. We provide a cost-effective RNA-Seq library synthesis protocol that is fast, starts with tissue, and is high-throughput from tissue to synthesized library. We have also designed and report a set of 96 unique barcodes for library adapters that are amenable to high-throughput sequencing by a large combination of multiplexing strategies. Our developed protocol has more power to detect differentially expressed genes when compared to the standard Illumina protocol, probably owing to less technical variation amongst replicates. We also address the problem of gene-length biases affecting differential gene expression calls and demonstrate that such biases can be efficiently minimized during mRNA isolation for library preparation.